Pengaturan Warisan Beda Agama Dipandang Dari Hukum Islam Dan Hukum Perdata - Rahmadani, Gema (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
The heir who dies is a Muslim, so his inheritance rights are Islam, so that the settlement of inheritance for heirs can be carried out according to Islam and can be resolved in the Religious Courts. If the heir has a different religion from the heir, then the inheritance settlement is carried out in the District Court. Heirs of different religions still receive inheritance through a mandatory will with the acquisition of inheritance rights for heirs of different religions whose share is not more than 1/3 of the inheritance. So that in Islamic law, non-Muslim heirs of different religions with Muslim heirs still get their rights as heirs through a mandatory will. Keywords: Inheritance, Religion, Islamic Law, Civil Law